Training to create HOTS problems based on analyzing level of Bloom’s taxonomy for Mathematics Junior High Schools Teachers in Kabupaten Banjar. - Rahmatya Nurmeidina; Iin Ariyanti (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2020)
Higher Order Thinking Skills (HOTS) is an important ability for students. The teachers can give HOTS problems to students started from the analyzing level, as preliminary habituation before they give more complex level (evaluating and creating level). Therefore, it is important to give training to create HOTS problem based on analyzing level of Bloom’s Taxonomy for mathematics teachers. This community service activity took place at Martapura 1 Junior High School. Participants in this activity were 30 Mathematics teachers in Kabupaten Banjar. The methods of implementing this training are presentations, demonstrations, and discussions. The advantage from the results of this activity are increasing the teacher's understanding of the HOTS concept in analyzing level, providing experience for the teacher to solve HOTS problems as well as creating HOTS problems. Thus, teachers are expected can give HOTS problems for students in mathematics learning and they can create HOTS problems for students' final exams.